PEMBELAJARAN MODEL GAMBAR DAN SUGESTI IMAJINER TERHADAP KEMAMPUAN MENULIS PUISI DAN SASTRA - Lili Sadeli (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2020)
Abstract - Growing the interest of writing students takes the teacher's efforts to motivate with various interesting and not boring teaching models. Through this research to obtain the effectiveness of picture and picture models and imaginary suggestions on the interest in writing literature poetry of grade VIII students at SMP Swadaya I Bandung. Simple research among others group 1 grade VIII-B using pinture and picture models and group 2 through imaginary suggestion, with quasi design design experiments with the form of model nonequivalent control group design. From the results of the study it is known that the image model is more effective and attractive to students, than the second model of imaginary suggestion in fostering the interest of learning to write poetry literary texts of students, especially in grade VIII junior high school. Abstrak. Menumbuhkan minat menulis siswa dibutuhkan upaya guru untuk memotivasi dengan berbagai model pengajaran yang menarik dan tidak membosankan. Melalui penelitian ini untuk memperoleh efektifvitas model picture and picture dan sugesti imajiner terhadap minat menulis puisi sastra siswa kelas VIII di SMP Swadaya I Bandung. Simple penelitian antara lain grup 1 kelas VIII-B menggunakan model pinture and picture dan grup 2 melalui sugesti imajiner, dengan desain quasi eksperimen desain dengan bentuk model nonequivalent control group desain. Dari hasil penelitian diketahui bahwa model gambar lebih efektif dan menarik bagi siswa, ketimbang model kedua sugesti imajiner dalam menumbuhkan minat belajar menulis puisi sastra teks siswa, khususnya di kelas VIII SMP.